2015
DOI: 10.1016/j.euroneuro.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 receptor stimulation modulates the formation and retrieval of novel object recognition memory: Role of the prelimbic cortex

Abstract: Previous studies have shown that dopamine D1 receptor antagonists impair novel object recognition memory but the effects of dopamine D1 receptor stimulation remain to be determined. This study investigated the effects of the selective dopamine D1 receptor agonist SKF81297 on acquisition and retrieval in the novel object recognition task in male Wistar rats. SKF81297 (0.4 and 0.8 mg/kg s.c.) given 15 min before the sampling phase impaired novel object recognition evaluated 10 min or 24 h later. The same treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
1
44
0
1
Order By: Relevance
“…into the mPFC induced a dose-related impairment in object recognition encoding and retrieval (Pezze et al, 2015). Although these results appear conflicting, the authors propose that NOR memory requires an optimal level of D 1 receptor stimulation in the mPFC and may reflect an inverted U-shaped function (Pezze et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…into the mPFC induced a dose-related impairment in object recognition encoding and retrieval (Pezze et al, 2015). Although these results appear conflicting, the authors propose that NOR memory requires an optimal level of D 1 receptor stimulation in the mPFC and may reflect an inverted U-shaped function (Pezze et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although these results appear conflicting, the authors propose that NOR memory requires an optimal level of D 1 receptor stimulation in the mPFC and may reflect an inverted U-shaped function (Pezze et al, 2015). The role of dopamine in the PFC has been further investigated using other selective dopamine receptor agonists and antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…As this is an innate tendency, novel object recognition (NOR) procedures offer advantages over many learning and memory tasks in that NOR can be studied without training or the use of positive (e.g., food) or negative (e.g., footshock) reinforcers (Lyon et al 2012). Furthermore, by selecting an appropriate phase for drug administration, the task can be utilized to distinguish the effects of neuropharmacological manipulations on acquisition, consolidation, and/or retrieval of visual learning and memory (King et al 2004;Pezze et al 2015). The neurobiological substrates of recognition memory have been extensively studied (Winters et al 2008;Brown et al 2010;Warburton and Brown 2010) and a key role has been identified for plasticity within the perirhinal cortex (Bussey et al 1999;Brown and Aggleton 2001;Banks et al 2012).…”
Section: United Kingdommentioning
confidence: 99%
“…The NOR task was based on previously established protocol (Pezze et al 2015). Experiments 1 and 2 were run over a 6 d cycle in a within-subjects design.…”
Section: Nor: Behavioral Proceduresmentioning
confidence: 99%
“…IP injection of SCH-23390 [11], or by D1 activity facilitation via SKF81297 microinfusion in the prefrontal cortex [12].…”
mentioning
confidence: 99%